Effect of dietary essential oil of oregano on performance parameters, gastrointestinal traits, blood lipid profile, and antioxidant capacity of laying hens during the pullet phase - Johnson, Alexa M.; Anderson, Gracie; Arguelles-Ramos, Mireille; Ali, Ahmed A. B. (Frontiers in Animal Science, 2022)
Many benefits have been found in supplementing essential oils such as oregano oil (EOO) to poultry, including increased bodyweight gain, antioxidant activity, and better gastrointestinal morphology. However, few studies tested the influence of EOO supplementation on laying hens and reported conflicting results regarding its efficacy in improving their health and performance. Therefore, we aimed to explore the effects of dietary EOO on performance, gastrointestinal (GIT) traits, blood lipid, and antioxidant capacity in laying hens during the rearing phase. A total of 300-day-old Hy-line-Brown chicks were used, and treatment diets consisted of corn-soybean based either without (CON) or with EOO (Ecodiar, 0.275 g/kg diet). Birds were randomized across treatments with five pens/treatment and 30-birds/pen. Pen weights and feed rejected were recorded every two weeks (1-17 weeks of age), to calculate daily feed intake (ADFI), body weight (BW), and daily weight gain (ADWG). At 11 and 14 weeks of age, blood samples were collected from 3 birds/pen and analyzed for blood lipids and antioxidant levels, and 5-birds/treatment were euthanized, and GIT traits were tested. Differences in measured parameters across weeks and between treatments were assessed using GLMM with Tukey's Post hoc test applied to significant results in R 3.3.1 (α set at 0.05). Body weights at weeks 3, 11, 13, and 17 were significantly higher in the EOO group compared to the CON group (all P≤0.05), ADWG was significantly higher in EOO birds compared to CON birds at 9 and 13 weeks old (all P≤0.05), while no significant differences in ADFI were observed between treatments across weeks of the trials. At both 11 and 17 weeks old, triglyceride levels were significantly lower, while high-density-lipoprotein levels were higher in EOO (all P≤0.05). Malondialdehyde levels were lower in the EOO group versus CON (p=0.01), while EOO birds had higher glutathione levels (p=0.01) than CON. Finally, at 12 weeks old, the weight of the entire GIT and empty gizzard were higher in the EOO group versus CON (all P≤0.05), while liver and spleen weights were not significantly different between groups. In conclusion, dietary oregano supplementation exerted promoting effects on the performance of Hy-Line Brown pullets.